1999
DOI: 10.1080/02626669909492202
|View full text |Cite
|
Sign up to set email alerts
|

Particle size characteristics of suspended sediments and subglacial hydrology of Dokriani Glacier, Garhwal Himalaya, India

Abstract: Diurnal and seasonal variations in particle size characteristics of suspended sediments of Dokriani glacier meltwater were studied during the 1994 ablation period (May-October). Diurnal suspended sediment concentration curves exhibit two prominent peaks from May to mid-August and only one peak during the rest of the ablation period. The first peak resulting from dominance of fine and medium sand contributed to the rising limb of the diurnal hydrograph, whereas the second peak was dominated by fine and medium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…This latter observation confirms that these high TOC values are not an artifact controlled by grain size but indicate significant addition of soil‐derived material to the Narayani sediment load during the premonsoon period. The smaller grain size during that time is also compatible with a soil signature (supporting information Figures S9 and S11), although we cannot rule out alternative explanations such as low discharge and turbulence limiting the coarse grain suspension and/or glacial fine‐sediment contributions (Thayyen et al, ).…”
Section: Discussionmentioning
confidence: 64%
“…This latter observation confirms that these high TOC values are not an artifact controlled by grain size but indicate significant addition of soil‐derived material to the Narayani sediment load during the premonsoon period. The smaller grain size during that time is also compatible with a soil signature (supporting information Figures S9 and S11), although we cannot rule out alternative explanations such as low discharge and turbulence limiting the coarse grain suspension and/or glacial fine‐sediment contributions (Thayyen et al, ).…”
Section: Discussionmentioning
confidence: 64%
“…This study has not analyzed the supraglacial sediment characteristics, but other studies carried out in the nearby region suggest that supraglacial sediment generally follows coarsely skewed patterns, whereas the sediment contribution from subglacial drainage systems usually follows symmetrical to finely skewed patterns (Thayycn et al, 1999;Owen et al, 2003). While analyzing seasonal distribution, we observed that particle sizes of the suspended sediments during peak melting seasons do show negatively skewed patterns.…”
Section: Subglacial Sediment Evacuationmentioning
confidence: 77%
“…The early occurrence of peak melting, when the total melt period is six months, supports the idea of reduced effectiveness of the system to produce sediment as the season progresses (Raymond et al, 1995). Localized variations in SSC with diurnal discharge could be due to translatory flow of hydraulically activated gradient within the subglacial aquifer that is controlled by the bed topography and water pressure variations in the channel (Gurnell and Fenn, 1984;Thayycn et al, 1999) and by hysteresis (Singh et al, 2005). From the point of view of particle size, low flow velocity mostly allows finer sediment to evacuate leaving behind coarser particles for the peak melt period (Fig.…”
Section: Seasonal Evolution Of Glacial Meltwater and Suspended Sedimentmentioning
confidence: 90%
“…A large number of published work on the hydrological studies related to Higher and Lesser Himalayan Rivers and glaciers have focused to understand the glacial runoff characteristics, water chemistry, silicate weathering and CO 2 consumption, erosion rates, etc. (Abbas and Subramanian, 1984;Sarin and Krishnaswami, 1984;Raymo and Ruddiman, 1992;Hasnain and Chauhan, 1993;Bhatt and Saklani, 1996;Hasnain and Thayyen, 1999;Pandey et al, 1999;Thayyen et al, 1999;Jain, 2002;Hasnain, 1998, 2002;Bickle et al, 2003;Vance et al, 2003;Singh et al, 2005;Chakrapani, 2005b;Varun and Kireet, 2006 and many others). Most of these studies were based on parameters deduced from seasonal samples collected from the glaciers, and in fluvial studies considered water flow only at three locations namely, Alaknanda River at Devprayag, Bhagirathi River at Devprayag and Ganga River at Rishikesh, which were made available by Rao (1975).…”
mentioning
confidence: 92%